Literature Study: Analysis of the Implementation of the BPJS Kesehatan Patient Referral System in Community Health Centers - Dina, Putri; Devi, Sri; Rahmawati, Nurul; Hajijah Purba, Sri (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
A referral system is a system that organizes healthcare and is responsible for addressing health cases or problems, regulating the flow of referrals and referrals for health check-ups. This referral system requires the participation of the government as policymaker, the community as service users, and health services as drivers of success. This study aims to analyze the implementation of the referral system in community health centers by reviewing previous research. This study used a literature review method, examining 10 journals related to the implementation of the BPJS Kesehatan patient referral system in community health centers. The results indicate that the referral system in most community health centers is operating in accordance with applicable Standard Operating Procedures (SOPs). However, several obstacles remain, such as unstable internet access, poor road access, ineffective communication, and limited medical facilities. Evaluation and improvements are ongoing to address these obstacles. In conclusion, the referral system as a whole is operating in accordance with existing SOPs, although improvements are still needed in several aspects to achieve the desired efficiency and effectiveness.